A black hole attack model using topology approximation for reactive ad–hoc routing protocols. (30th April 2014) - Badenhop, Christopher W.; Mullins, Barry E.
This paper examines one particular network degradation attack, the Black Hole attack, to determine if an analytical model can be used to predict the impact of this attack on ad–hoc networks. An analytical Black Hole attack model is developed for reactive ad–hoc network protocols dynamic source routing (DSR) and ad–hoc on–demand distance vector (AODV). Hypercube topologies are used to approximate prototypical ad–hoc topologies to derive the hopdistance density function for selected topology classes. An experiment is conducted to compare the expected packet loss of the analytical model against simulated Black Hole attacks on a variety of topology classes. The results show that the model describes the general order of growth for packet loss as a function of the number of Black Holes in a given network. ANOVA tests identify that the relative location of the Black Hole, source, and destination within a topology significantly impacts the packet loss performance of a Black Hole attack.